How Should I Dress? Understanding the Clothing Consumption of Businesswomen in the Clothing Market - Silva, Marianny Jessica de Brito (2018)
Purpose: This article aims to analyze the relationship between businesswomen in the clothing industry and the clothes they chose to wear. Method: This research is qualitative and studies multiple cases via in depth interviews, investigating them through the semantic-pragmatic art of conversation. Originality/relevance: The main originality of this paper is in the interviewees, as they are businesswomen in the fashion industry themselves. Studies in this industry tend to analyze the final consumer and the retail strategies adopted to influence sales, but a focus on understanding these entrepreneurs as consumers and end users of the products has not been explored. Results: The findings of this study point to the following results: businesswomen convey how they would like to be perceived through the clothes they buy and wear; the profession and the role played may influence the choice of the product to be purchased; the buying process is neither planned nor systematic; clothing can be an indication of the managerial style and can also reflect the social role being played, demonstrate individuality, economic status and the groups of affiliation or aspiration of these female entrepreneurs. Theoretical contributions: This study offers a theoretical advancement in identifying a very interesting closure of the cultural circuit in which the creators have been turned into their own creations. The analyzed businesswomen create objects of consumption in their companies to be desired by the consumers; and are themselves transformed by means of the desires and buying behavior, into the objects of consumption and images of success to be acquired and reproduced.